IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE USE OF DIGITAL LEARNING MEDIA - Nur Hidayat; Suryadi Suryadi (Universitas Tanjungpura, 2023)
The success of a learning including by utilizing learning media. But in fact the use of learning media is still not used optimally. digital learning media is one of the media to improve student learning outcomes. This study aims to determine the use of digital learning media to improve student learning outcomes. The design of this study was a true experimental study with a Pretest-Posttest Group Design. Learning outcomes data were obtained through pretest and posttest activities. The sample was 80 students who were taken randomly by adjusting the conditions and research objectives. There is a significant difference in the posttest results of the experimental class and the control class, this is evidenced by the value of Fo. For the value is 5.225 and Sig is 0.025 < 0.05. This means that there is a difference in the interaction effect of using digital learning media to improve student learning outcomes